Assessment on The Challenges of Using ICT for Teaching Undergraduates Students in Federal University Dutsin-Ma, Katsina - Dada, Kayode Sunday John (Journal in Teaching and Education Area, 2025)
The integration of Information and Communication Technology (ICT) in higher education has revolutionized teaching and learning worldwide, but its implementation in developing regions like Nigeria encounters substantial obstacles. This empirical study evaluates the challenges of utilizing ICT for teaching undergraduate students at Federal University Dutsin-Ma (FUDMA), Katsina, Nigeria. A cross-sectional survey was administered to 200 participants, including lecturers and students, employing structured questionnaires to assess ICT tool usage, perceived challenges, and prospective remedies. Results indicate varying levels of tool adoption: Learning Management Systems (LMS) like Moodle showed high usage (M=4.16, SD=0.63), followed by interactive whiteboards (M=4.44, SD=0.63), video conferencing such as Zoom (M=3.69, SD=0.91), PowerPoint (M=2.84, SD=1.13), email (M=2.78, SD=0.89), and social media (M=1.98, SD=0.76). Challenges were rated for severity, with large class sizes (M=4.49, SD=0.57) and lack of skills (M=4.46, SD=0.62) emerging as most critical, alongside funding issues (M=4.24, SD=0.63), electricity problems (M=3.97, SD=0.69), poor infrastructure (M=3.51, SD=0.73), and resistance to change (M=1.73, SD=0.66). These impediments restrict effective ICT incorporation, widening gaps in resource-limited settings. The study highlights the necessity for strategic measures to improve ICT effectiveness in undergraduate education. One primary recommendation is establishing mandatory ICT training initiatives for staff and students to enhance digital proficiency and assurance, thereby addressing skill deficiencies and promoting enduring tech integration. Outcomes advance discussions on ICT in African tertiary institutions, stressing tailored approaches to surmount infrastructural and workforce limitations.